Augmented Reality Introduction The Engineering and Computer of Harapan Medan University Using Markerbased Tracking Method - Nurjamiyah, N; Elsera, Marina; Ashar, Khairil (IJISTECH (International Journal of Information System and Technology), 2023)
Developing technology provides convenience in almost every field. One of them is the introduction of a campus that will be an option for prospective students. Almost every campus promotes its campus by using banners, brochures, and others. The use of flyer or brochure for introduction the Faculty of Engineering and Computers Harapan Medan University was less efficient because of student candidates were not familiar with the Faculty of Engineering and Computers Harapan Medan University. The use of Augmented Reality will attract the interest of student candidates to become more familiar with the Faculty of Engineering and Computers Harapan Medan University. The method used for Augmented Reality is markerbased tracking, and for system development method is using waterfall. The application is built using Unity3D and uses Vuforia as the software development kit, and also uses C#(Sharp) for its programming language. Based on the results obtained, the system is running well as desired, such as displaying 3D of Faculty of Engineering and Computers Harapan Medan University Building and the location of the FTK Building. Augmented Reality provides a better picture of how access, buildings, locations and administrative centers are in Faculty of Engineering and Computers Harapan Medan University.